Transformational Leadership in Islamic Education: Strengthening Institutional Innovation in The Era of Disruption - Musaddad, Ahmad (Education Reserach Center, 2025)
The transformation of Islamic education in the era of disruption demands a leadership approach that is not only visionary but also rooted in spiritual and ethical values. This article provides an in-depth examination of the Islamic transformational leadership model, which integrates prophetic values, principles of adaptation and innovation, as well as collaborative and communicative practices in response to institutional challenges faced by madrasahs and Islamic higher education institutions. Through a systematic literature review and thematic synthesis of various academic sources, it is found that transformative Islamic leadership can promote the improvement of educational quality by shaping an inclusive, ethical, and maslahat-oriented learning ecosystem. Nevertheless, the implementation of this model faces cultural, structural, and normative resistance, requiring policy adjustments, leadership training based on prophetic values, and the strengthening of participatory governance. This article affirms that Islamic transformational leadership is not merely a normative concept, but a strategic praxis that can reinforce the role of Islamic education as a catalyst for equitable and sustainable social change.